Jerusalem Council: A Paradigm for a Synodal Church - thonippara, Francis (Asian Horizons, 2020)
The essence of Christian religion is communion. Synodal and conciliar activities were very common in the history of the first millennium Church. The Jerusalem Council (49 CE) is a paradigm for regaining the collegial, or synodal or participatory character of the Church where all layers of faithful were consulted before arriving at a solution by the “Apostles and Elders.” The greatest ecclesiological contribution of the Second Vatican Council is the re-discovery of the communion and collegial character of the Church. The establishment of the Synod of Bishops and its regular meetings to a great extent express the collegial character of the Church. Pope Francis is very much for a synodal Church. Through his Apostolic Constitution Episcopalis Communio (2019) expressed his desire for the synodal Church, taking lot of inspiration from the Jerusalem Council. Going back to the Jerusalem Council model of the functioning of the Church will also encourage ecumenism. The Spirit’s abiding presence in the Church guiding it to all truth is seen when the Church comes together in council.